2009
DOI: 10.1037/a0014577
|View full text |Cite
|
Sign up to set email alerts
|

More than child's play: Variable- and pattern-centered approaches for examining effects of sports participation on youth development.

Abstract: The authors used data from Grades 5 through 7 of the longitudinal 4-H Study of Positive Youth Development to assess relations among sports participation, other out-of-school-time (OST) activities, and indicators of youth development. They used a mixture of variable- and pattern-centered analyses aimed at disentangling different features of participation (i.e., intensity, breadth). The benefits of sports participation were found to depend, in part, on specific combinations of multiple activities in which youths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
3
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 58 publications
9
142
3
6
Order By: Relevance
“…For instance, the use of person-centered approaches to cluster youth into meaningful OST program profiles would provide insight into the impact of participation in multiple activities simultaneously on the development of specific indicators of PYD, including character attributes (Zarrett et al, 2009). Finally, whereas we controlled for several individual and family characteristics to reduce the risk of omitted variable bias, it is possible, through selection effects, that youth who are highly engaged in OST programs are also more likely to demonstrate positive development in other contexts of their lives as well when compared to less engaged youth.…”
Section: Future Directionsmentioning
confidence: 99%
“…For instance, the use of person-centered approaches to cluster youth into meaningful OST program profiles would provide insight into the impact of participation in multiple activities simultaneously on the development of specific indicators of PYD, including character attributes (Zarrett et al, 2009). Finally, whereas we controlled for several individual and family characteristics to reduce the risk of omitted variable bias, it is possible, through selection effects, that youth who are highly engaged in OST programs are also more likely to demonstrate positive development in other contexts of their lives as well when compared to less engaged youth.…”
Section: Future Directionsmentioning
confidence: 99%
“…In turn, youth participation in organized OST activities such as sports, after-school community programs (YD programs), and extracurricular activities (school-based), has been linked with multiple indicators of positive functioning (e.g., Mahoney, Vandell, Simpkins, & Zarrett, 2009;Zarrett, Fay, Li, et al, 2009;Zarrett, Fay, Peltz, et al, 2007) including physical health (e.g., lower rates of obesity; Mahoney, Lord & Carryl, 2005a;Vandell, Pierce & Dadisman, et al, 2005). For example, Mahoney et al (2005a) tracked a sample of disadvantaged children over a 3 year period (ages 5 to 8 years old) and found that, after controlling for earlier measures of BMI and demographic factors, those who participated in after-school programs (ASPs) showed less marked increases in BMI and significantly lower rates of obesity than similar children who did not participate in ASPs.…”
Section: Organized Ost Programs and Youth Obesitymentioning
confidence: 99%
“…The goal of this special section is to provide initial research about such context-specific instances of the thriving process. The articles in this special section focus on the two contexts that, together, involve the greatest investment of youth time, the school and out-of-school time sports programs (e.g., Balsano et al 2009;Elmore 2009;Zarrett et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…1 may be used to summarize the contributions to this special section. These contributions advance research about youth thriving by exploring the features of the process that exist within two of the key contexts of youth development, school and outof-school-time (OST) programs involving youth participation in sports; such participation is the major instance of OST activity among youth (e.g., Balsano et al 2009;Zarrett et al 2009). Across the articles in this special section, the reported data provide an important means to appraise the nature of the similarities or differences in thriving across key contexts of youth.…”
Section: Introductionmentioning
confidence: 99%